Peran Undang-Undang No. 13 Tahun 2003 Tentang Pemutusan Hubungan Kerja Di Kota Medan - Harahap, Herlina Hanum; Lubis, Muhammad Ridwan; Hartono, Budi (Universitas Islam Sumatera Utara, 2024)
The working time provisions above also only regulate the working time limit for 7 or 8 days and 40 hours a week and do not regulate when working time or hours begin and end. Arrangements for the start and end of working time or hours every day and during the week, must be clearly regulated as needed by the parties in the Work Agreement, Company Regulation (PP) or Collective Labor Agreement (PKB). The problem raised in this research journal is how the obstacles faced by Law No. 13 of 2003 concerning Decisions on Employment Relations. This research approach method uses a normative juridical approach. The normative approach method is used to analyze laws and regulations relating to Termination of Employment Relations. The results of this research journal are not synchronized between legislation and termination of employment in the field. Many company employees do not receive wages in accordance with law no. 13 of 2003. Keyword: Termination, Employment Relationship